2002
DOI: 10.1002/bip.10158
|View full text |Cite
|
Sign up to set email alerts
|

A conformational analysis of leucine enkephalin as a function of pH

Abstract: The conformations of Leu enkephalin in aqueous solution have been investigated as a function of pH using molecular dynamics simulations. The simulations suggest the peptide backbone exists as a mixture of folded and unfolded forms (approximately 50% each) at neutral pH, but is always unfolded at low or high pH. The folded form at neutral pH possesses a 2 --> 5 hydrogen bond and a close head to tail separation. No significant intramolecular hydrogen bonding of the carbonyl oxygens was observed in either the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 30 publications
2
39
1
Order By: Relevance
“…Another recent simulation of YGGFL, however, predicted a narrower distribution of Tyr-Phe distances with a peak at 9 Å at neutral pH 11. Our simulations predicted a much wider conformational heterogeneity, including broader Tyr-Phe distance distribution than reported in ref 11. Compared to our calculations, the simulations in that work used the GROMOS force field, a different non-bond truncation scheme, a different water model, about 50% fewer waters, and much shorter trajectories of 5-10 ns.…”
Section: Resultsmentioning
confidence: 90%
“…Another recent simulation of YGGFL, however, predicted a narrower distribution of Tyr-Phe distances with a peak at 9 Å at neutral pH 11. Our simulations predicted a much wider conformational heterogeneity, including broader Tyr-Phe distance distribution than reported in ref 11. Compared to our calculations, the simulations in that work used the GROMOS force field, a different non-bond truncation scheme, a different water model, about 50% fewer waters, and much shorter trajectories of 5-10 ns.…”
Section: Resultsmentioning
confidence: 90%
“…Their results for the distribution of urea and glycerol around Ribonuclease A at low cosolvent concentrations were in good agreement with experiment, and a correlation was observed between the number of cosolvents and the number of water molecules in the vicinity of the protein. We have applied computer simulations and KB theory to study the effects of NaCl on the equilibrium thermodynamics of folded and unfolded forms of the leucine enkephalin pentapeptide [83,166]. This study demonstrated that a combined simulation and KB approach is feasible for small systems.…”
Section: Computer Simulation Of Cosolvent Effectsmentioning
confidence: 93%
“…In the case of [Leu]enkephalin, van der Spoel and Berendsen25 conclude that the zwitterionic form of this peptide in water is very flexible but seems to have a predilection for compact conformations. In a similar vein, Aburi and Smith28 gives a detailed description of the conformational dynamics of [Leu]enkephalin as a function of pH, and concludes that at neutral pH a mixture exists between folded and unfolded states with only a slight predominance of folded conformations (the actual distribution of these states seems to depend on the type of fit that they use in their clustering method).…”
Section: Introductionmentioning
confidence: 93%
“…Several detailed simulations of [Leu]enkephalin and [Met]enkephalin at neutral pH in aqueous solution have been reported recently25–28; however, none of these seek to directly compare the backbone and side‐chain dynamics of [Leu]enkephalin with those of [Met]enkephalin. In the case of [Met]enkephalin, Carlacci26 reports that in the zwitterionic form the backbone predominantly remains in one of several folded states, but a mechanism is provided for transitions into an extended backbone conformation provided the zwitterionic form is somehow neutralized.…”
Section: Introductionmentioning
confidence: 99%